Coupling Zero-Valent Iron and Fenton processes for degrading sulfamethazine, sulfathiazole, and norfloxacin - Fornazaria, Ana Luiza; Labriola, Vanessa Feltrin; Da Silva, Bianca Ferreira [UNESP]; Castro, Lucas Fernandes; Perussi, Janice Rodrigues; Vieira, Eny Maria; Azevedo, Eduardo Bessa (Elsevier, 2021)
In this study, the degradation of three antibiotics - sulfamethazine (SMT), sulfathiazole (STZ), and norfloxacin (NOR) (1.0 mg L-1 each) - was achieved by coupling the Zero-Valent Iron Process using supported metallic iron nanoparticles (nZVI) to the Fenton one. The system was operated in single-pass continuous-flow mode at steady-state regime (after 15 min). The nanoparticles were packed into a fixed-bed reactor and characterized by several techniques (SEM, EDX, TEM, and XRD). The degradation experiments were performed according to a 22 factorial design, in which the effects of pH and flow rate (Q) were studied. The degradation conditions were: initial pH = 3.0 and Q = 20 mL min-1· H2O2 was then continuously added to the effluent of the nZVI reactor (containing Fe2+) in order to perform the Fenton process in the following mixing vessel (H2O2 concentration of 34 mg L-1). At the exit of the system, the antibiotics concentrations were below the detection limit of the chromatographic method (40 μg L-1) and dissolved iron was below 1.0 mg L-1. Sixteen degradation products (DPs) of SMT, STZ, and NOR were detected and identified using HPLC-MS/MS. Their ecotoxicological endpoints (LC50, EC50, and ChV) for three trophic levels were estimated with the aid of the ECOSAR 2.0 software. No ecotoxicity was generated towards Lactuca sativa during treatment. The proposed system was able to partially remove the antimicrobial activity (Escherichia coli) of both sulfonamides (16%) and NOR (47%).
Keywords: Antibiotics; Antimicrobial activity; AOP; Nanoparticles; ZVI